Proposing A Nonmainstream Concept of Corporate Social Responsibility through Islamic Perspective - Rahmanti, Virginia Nur; Agustia, Dian; Setiawan, Achdiar Redy (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2024)
Abstract: Proposing A Nonmainstream Concept of Corporate Social Responsibility through Islamic Perspective Purpose: This article aims to criticize the concept of CSR from an Islamic perspective. Method: Researchers employed hyper-post phenomenology as a methodological approach. Results: The results show that the practice of CSR by Islamic banks in Indonesia has shifted from social to material goals. CSR is only a legitimization tool for "sharia" and from Islamic banks to reap greater profits. Novelty: This research uses the Islamic paradigm, which calls for interdimensional unity by placing spiritualism as its epicenter. Contribution: This article creates a policy framework for integrating social programs with Islamic banks' objectives to achieve falah. Abstrak: Mengusulkan Konsep Tanggung Jawab Sosial Perusahaan yang Nonmainstream dalam Perspektif Islam Tujuan: Artikel ini bertujuan untuk mengritisi konsep CSR dari perspektif islam. Metode: Metode penelitian ini adalah hyper-post-fenomenologi Hasil: Hasil menunjukkan bahwa praktik CSR oleh bank syariah di Indonesia telah terbukti terjadi pergeseran dari tujuan sosial ke tujuan materi. CSR nyatanya hanya menjadi alat legitimasi atas "sharia" dan dari bank-bank Islam untuk meraup laba yang lebih besar. Kebaruan: Penelitian ini menggunakan paradigma Islam yang menghendaki adanya kesatuan antardimensi dengan menempatkan spiritualisme sebagai episentrumnya. Kontribusi: Artikel ini berkontribusi pada pembuatan kerangka kebijakan untuk mengintergrasikan program sosial dengan tujuan bank syariah sendiri, sehingga dapat tercapai falah.